Kajian Filosofis Pendidikan Agama Kristen dalam Kehidupan Orang Percaya di Era Posmodern - Marbun, Lidia; Saragih, Jan Romi Perdana (Sekolah Tinggi Teologi IKAT Jakarta, 2022)
AbstractChristian religious education cannot be separated from philosophy, because after all the Bible, especially the New Testament, is influenced by philosophy. One of the great foundations of Christian religious education is the philosophical foundation. But there are significant differences between secular philosophy and Christian philosophy, namely regarding the philosophical basis to the practical. So, in understanding the principles and practice of Christian religious education, it is necessary to have a solid foundation in eroding secular philosophies that greatly affect the church and students so that it does not achieve the goals of Christian religious education being held because the philosophy that enters Christian religious education emphasizes the autonomy of the ratio compared to authority. Allah is the causality of everything. Philosophy is very systematic and critical in drawing conclusions, not infrequently eventually this rationality makes the Bible lose its place as the main source in explaining metaphysics, epistemology, and axiology which is replaced with logical thinking which often even contradicts the Scriptures. By using qualitative methods, the author examines the philosophical meaning of Christian Religious Education. AbstrakPendidikan Agama Kristen tidak dapat dipisahkan dari filsafat, karena bagaimanapun Alkitab khususnya Perjanjian Baru dipengaruhi oleh filsafat. Salah satu landasan besar mengenai pendidikan agama Kristen adalah landasan filosofis. Tetapi ada perbedaan yang signifikan antara filsosofi sekuler dan filosofi Kristen, yaitu mengenai dasar filosofis hingga praktisnya. Maka dalam memahami prinsip dan praktis pendidikan agama Kristen, perlu fondasi yang kokoh dalam mengikis filosofi sekuler yang sangat mempengaruhi gereja dan peserta didik sehingga tidak mencapai tujuan dari pendidikan agama Kristen tersebut diselenggarakan, dikarenakan filsafat yang masuk kedalam pendidikan agama Kristen begitu menekanankan otonomi rasio dibandingkan otoritas Allah sebagai kausalitas segala sesuatunya. Filsafat sangat sistematis dan kritis dalam mengambil kesimpulan, tidak jarang akhirnya rasionalitas tersebut membuat Alkitab kehilangan tempat sebagai sumber utama dalam menjelaskan metafisika, epistemologi, maupun aksiologi yang digantikan dengan pemikiran logika yang bahkan kerapkali menentang Kitab Suci Alkitab. Dengan menggunakan metode kualitatif, penulis mengkaji pemaknaan filosofis Pendidikan Agama Kristen.